EFEKTIFITAS PENGGUNAAN METODE FLIPPED CLASSROOM DENGAN PENDEKATAN KOOPERATIF LEARNING UNTUK PEMBELAJARAN MAHARAH ISTIMA’ PADA SISWA SMP ISLAM HASANUDDIN MALANG - Amelia, Ulfi; Bahruddin, Uril; Fikri, Shofil (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Listening instruction at SMP Islam Hasanuddin Malang still relies on traditional, teacher-centered methods, resulting in low student engagement and underutilization of technology. The aim of this study is to investigate the implementation of the flipped classroom method combined with a cooperative learning approach in teaching listening skills, and to evaluate its effectiveness for students at SMP Islam Hasanuddin Malang. This study adopts a quantitative approach and employs an experimental research method. Data collection techniques include observation, documentation, and testing. Data analysis involves normality testing, homogeneity testing, and hypothesis testing using the SPSS 21 software. The findings indicate that the implementation of the flipped classroom method with a cooperative learning approach in teaching listening skills consists of several stages: the teacher prepares learning materials in the form of Arabic audio recordings and distributes them for students to study independently at home. During face-to-face sessions, the teacher reviews the material with the students. Students work in small groups to discuss the content, complete exercises based on the audio texts, and share their understanding with their peers. Evaluation is conducted both individually and in groups, with dedicated sessions for self-reflection. The use of the flipped classroom method with a cooperative learning approach has been proven effective in teaching listening skills. This is supported by a statistical significance value of sig = 0.000, which is less than 0.05. Therefore, the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted.